2015
DOI: 10.7202/1033191ar
|View full text |Cite
|
Sign up to set email alerts
|

La prise en compte du français dans l’organisation des services en foyers de soins majoritairement anglophones au Canada

Abstract: L’accès aux services de santé en français préoccupe grandement les communautés francophones vivant en situation minoritaire. Le présent article offre un survol de l’espace francophone dans les résidences collectives d’aînés du Nouveau-Brunswick, de la Nouvelle-Écosse et de l’Ontario à la lumière d’une recherche exploratoire menée en 2012. L’analyse des données obtenues auprès d’aînés, d’aidants et du personnel, l’examen de la répartition géographique des résidences et de la p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Group cohesion among French-speaking residents did not seem to be prioritized, as a sample of predominantly Anglophone nursing homes in Ontario, New-Brunswick and Nova-Scotia were reported to tend to group individuals together based on their health status rather than having sections reserved for linguistic groups (Michaud et al 2015 ). While some staff members and residents alike indicated that services could be provided in either official language due to the fact that most residents are bilingual, certain Anglophone homes indicated that activities sometimes did take place in French, that French-speaking employees could provide services in the official minority language, and that meals could be adapted to the Francophone or Acadian culture (Michaud et al 2015 ). Additionally, the proximity of the nursing home to older adults’ family members was the most cited decision factor for Francophones when choosing a home (Michaud et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Group cohesion among French-speaking residents did not seem to be prioritized, as a sample of predominantly Anglophone nursing homes in Ontario, New-Brunswick and Nova-Scotia were reported to tend to group individuals together based on their health status rather than having sections reserved for linguistic groups (Michaud et al 2015 ). While some staff members and residents alike indicated that services could be provided in either official language due to the fact that most residents are bilingual, certain Anglophone homes indicated that activities sometimes did take place in French, that French-speaking employees could provide services in the official minority language, and that meals could be adapted to the Francophone or Acadian culture (Michaud et al 2015 ). Additionally, the proximity of the nursing home to older adults’ family members was the most cited decision factor for Francophones when choosing a home (Michaud et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…While some staff members and residents alike indicated that services could be provided in either official language due to the fact that most residents are bilingual, certain Anglophone homes indicated that activities sometimes did take place in French, that French-speaking employees could provide services in the official minority language, and that meals could be adapted to the Francophone or Acadian culture (Michaud et al 2015 ). Additionally, the proximity of the nursing home to older adults’ family members was the most cited decision factor for Francophones when choosing a home (Michaud et al 2015 ). In turn, housing options, access to a variety of services and social support were variables that contributed to allowing French-speaking minority older adults to age in place (Dupuis-Blanchard et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, it has not been the case. A number of studies carried out in Canada have shown that, in practice, universal access to health services in the official language of one's choice is far from being a reality (Michaud, Forgues & Guignard Noël, 2015), and that the minority Francophone population is up against major obstacles in terms of equitable access, quality health services and health outcomes comparable to the majority (Negura, Moreau & Boutin, 2014;Simard et al, 2015;van Kemenade, Bouchard, & Bergeron, 2015). This is why the late Mauril Bélanger, in his Bill C-202, An Act to Amend the Canada Health Act (linguistic duality), proposed adding linguistic duality as a condition that provincial health insurance plans would have to meet to qualify for the full cash contribution.…”
Section: One Federal Health Care Act and 13 Independent Health Care Delivery Jurisdictionsmentioning
confidence: 99%